Foreign body aspiration in children - Gül, Evrim; Çakmak, Muharrem; Gül, Yeliz; Gurger, Mehtap; Sarı, Mehmet Yusuf; Atescelik, Metin (My University, 2020)
Aim: Foreign body aspiration (FBA) is a life-threatening conditional. We aimed to share the results of FBA in children.Material and Methods: We evaluated retrospectively files of 61 patients between the ages 1-10 underwent rigid broncoscopy. It wereevaluated the types and anatomic localization of aspirated foreign bodies, the age distribution of children, treatment procedures. Theresults was assessed by Chi-square test or Fisher's exact test. P<0.05 was considered significant.Results: The mean ages were 3.29±1.91. 62% of the patients were male, and 38% were female (p<0.05). Aspirated foreign bodylocalized right in 38 patients, left in 13 patients, tracheal in 6 patients. Foreign body was observed in the right main bronch in 18patients, in the right lower lobe bronch in 19 patients, in the medium lobe bronch in 1 patients, in the left main bronch in 9 patients, inthe left lower bronchus in 4 patients. Bronchoscopies were negative in four patients, although foreign body aspiration is considered.Conclusion: FBAs are common in children. In children younger than 3 years are more common. The gold standard in treatment isrigid bronchoscopy. The incidence and severity of airway FBA can be reduced by parental education and public awareness.
Keywords: Acil Tıp; Pediatri